DEVELOPING MATERIALS FOR ESP (ENGLISH FOR SPECIFIC PURPOSES) CLASS - Umi Trisyanti (Jurnal Sosial Humaniora, 2025)
Some EFL teachers spend a great deal of time searching for textbooks appropriate to their learner’s needs. But these teachers usually discover that the chosen textbook does not contain exactly what their students require. In order to ensure that the language and content covered in the materials are suitable to the learners’ need and that the students are properly prepared for the real life situations of the target language, teachers are often required to write their own instructional materials from authentic sources. This paper presents a course outline to develop a material for ESP class that can be used by TEFL teachers with an ESP audience. The texts used for the materials development are taken from authentic sources.